Difusi Inovasi Aplikasi Tanggap Karawang: Studi Deskriptif Kualitatif Adopsi Aplikasi Tanggap Karawang dengan Pendekatan Teori Difusi Inovasi - Agustina, Aurelia; Yuni Dharta, Firdaus; Kurniansyah, Dadan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
The Karawang Response Application (“TANGKAR”) is a community aspiration service portal and online complaint platform for the people of Karawang, based on Android, web, SMS gateway, and social media. It aims to meet the community’s needs in channeling complaints through official government channels and monitoring the resolution process effectively and efficiently. This study examines the utilization of the TANGKAR Application by the Department of Communication and Informatics (Diskominfo) of Karawang Regency as the innovator, using the diffusion of innovation theory. It also evaluates the level of utilization of the TANGKAR Application and the extent of adoption among the community. The research method used is a descriptive qualitative method to describe the problems and research focus. Data collection techniques were conducted through interviews and documentation. Informant selection used purposive sampling. Based on data analysis, overall, the results of the study show that the diffusion of innovation of the TANGKAR Application has not run effectively. The results of this study indicate the forms of mass media communication and interpersonal communication. However, Solopos, as the innovator, relied more on mass media channels, since Solopos itself is the market leader in Solo City and owns many types of media that can reach a wider community. Meanwhile, interpersonal communication channels were more frequently used by adopters below the innovator level, as they tend to be persuasive in nature. The level of adoption of the Solopos e-paper has reached the Laggards stage, with the majority at the Late Majority stage, consisting of Solopos newspaper subscribers. Adoption in this study includes five stages: knowledge, persuasion, decision, implementation, and confirmation.